Konstruksi Pedagogis Al-Qur’an Surat Ali Imran Ayat 79 Tentang Kriteria Pendidik - Fikruzzaman, Daden; Julaeha, Siti; Dr, Suhrowardi (THORIQOTUNA: Jurnal Pendidikan Islam, 2024)
The purpose of this research is to find out how the criteria for educators are viewed from Law Number 14 of 2005 concerning Teachers and Lecturers, how some munfasir understand the Al-Qur'an, Surah Ali Imran Verse 79 regarding the criteria for educators and what is the pedagogical analysis of the Al-Qur'an Ali Imran's letter Verse 79. This research was carried out using a content analysis method on the Al-Qur'an Surah Ali Imran Verse 79 and the understanding of interpreters in the book, namely: Tafsir Ibnu Katsir, Tafsir Al-Misbah, Tafsir Al-Maraghi and Tafsir Al-Qur'anul Majid An-Nur. Thus, this research takes the form of a literature study. Tafsir books and other readings that are considered related to the subject matter in this research. The results of the research state that the pedagogical theory of the Koran, Surah Ali Imran verse 79, means that an educator must continue to teach and continue to learn. It is through this process of lifelong teaching and learning that humans are able to improve the quality of their lives. Several munfasir provide the same understanding of lapadz Rabbaniyina (Rabbani) in this verse, namely as a person who uses the logic of the Qur'an, carrying out a divine mission, a person who is wise or monotheism to Allah, act wisely, and always explore and study knowledge, teach knowledge, educate people and do good and evil. The criteria for educators based on Law Number 14 of 2005 concerning Teachers and Lecturers are to have pedagogical competence, personality competence, social competence and professional competence. Pedagogical analysis Qs. Ali Imran verse 79, that Qs. Ali Imran Paragraph 79, which was also adopted by Law Number 14 of 2005 concerning Teachers and Lecturers, requires that educators must have pedagogical competence, professional competence, personality competence and social competence